Brain metastasis PD-L1 and CD8 expression is dependent on primary tumor type and its PD-L1 and CD8 status. Issue 2 (27th August 2020) - Camy, Florian; Karpathiou, Georgia; Dumollard, Jean Marc; Magne, Nicolas; Perrot, Jean Luc; Vassal, Francois; Picot, Tiphanie; Mobarki, Mousa; Forest, Fabien; Casteillo, Francois; Hathroubi, Sirine; Froudarakis, Marios; et al.
Abstract : Background: Brain metastases (Bmets) are frequent; however, limited data exist on the efficacy of immunotherapy in these lesions. The aims of the study were to analyze the immunohistochemical expressions of programmed death ligand 1 (PD-L1) and CD8 in Bmets and to compare them with their expressions in paired primary tumors, as well as correlate the results with clinicopathological features. Methods: This is a retrospective study of 233 patients with Bmets and 111 paired primaries. Clinical, histological, and molecular data were recorded and compared with the immunohistochemical results of PD-L1 and CD8 expressions. The statistical analysis included χ 2 test, Cramer's V test, factorial analyses of variance, simple regression analysis, and Kaplan-Meier analysis with log-rank product limit estimation. Results: PD-L1 expression was found in 23.6% of Bmets and in 29.0% of primary tumors with concordant expression between them in 75.5% of cases. Bmets PD-L1 expression was associated with primary tumor PD-L1 expression and the primary tumor type. Significant CD8 peritumoral expression was found in 68.6% of Bmets and in 87.7% of primary tumors. CD8 expression was concordant between primary and metastatic tumors in 73.3% of cases. Bmets CD8 expression was associated with primary tumor CD8 expression and primary tumor type. PD-L1 expression was associated with CD8 expression in both primary and metastatic tumors. The concordance between primary and metastatic tumor PD-L1 expression was independent of all factors studied. The concordance between primary and metastatic CD8 expressions was marginally associated to the time of Bmets development. No prognostic role for PD-L1 and CD8 expression in Bmets was found. Conclusion: PD-L1 and CD8 Bmets expressions are associated with the primary tumor type and its PD-L1 and CD8 expressions. No factor predicts the discordance for PD-L1 expression, while time to Bmets development is associated with CD8 expression discordance.